Optimasi Transisi dari Pendidikan Anak Usia Dini (PAUD) ke Sekolah Dasar: Membangun Kesiapan Siap Sekolah melalui Tinjauan Literatur - Nurdianah, Andi; Suarni, Suarni; Kasim, Kasim; Nasir, Nasir (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2024)
This research aims to optimize the transition from Early Childhood Education (ECE) to Primary School (PS) by building school readiness. Utilizing an analysis of relevant articles published between 2020-2024 from Google Scholar with the keyword